Single-cell RNA sequencing identifies Fgf23-expressing osteocytes in response to 1,25-dihydroxyvitamin D3 treatment - Hanai, Ayako; Kawabata, Ayako; Nakajima, Kenta; Masuda, Kazuhiro; Urakawa, Itaru; Abe, Masahiro; Yamazaki, Yuji; Fukumoto, Seiji (Frontiers in Physiology, 2023)
Fibroblast growth factor 23 (FGF23), a hormone, mainly produced by osteocytes, regulates phosphate and vitamin D metabolism. By contrast, 1,25-dihydroxyvitamin D3, the active form of vitamin D, has been shown to enhance FGF23 production. While it is likely that osteocytes are heterogenous in terms of gene expression profiles, specific subpopulations of Fgf23-expressing osteocytes have not been identified. Single-cell RNA sequencing (scRNA-seq) technology can characterize the transcriptome of an individual cell. Recently, scRNA-seq has been used for bone tissue analysis. However, owing to technical difficulties associated with isolation of osteocytes, studies using scRNA-seq analysis to characterize FGF23-producing osteocytes are lacking. In this study, we characterized osteocytes secreting FGF23 from murine femurs in response to calcitriol (1,25-dihydroxyvitamin D3) using scRNA-seq. We first detected Dmp1, Mepe, and Phex expression in murine osteocytes by in situ hybridization and used these as marker genes of osteocytes. After decalcification, enzyme digestion, and removal of CD45+ cells, femoral bone cells were subjected to scRNA-seq. We identified cell clusters containing osteocytes using marker gene expression. While Fgf23 expression was observed in some osteocytes isolated from femurs of calcitriol-injected mice, no Fgf23 expression was detected in untreated mice. In addition, the expression of several genes which are known to be changed after 1,25-dihydroxyvitamin D3 treatment such as Ccnd2, Fn1, Igfbp7, Pdgfa, and Timp1 was also affected by calcitriol treatment in Fgf23-expressing osteocytes, but not in those lacking Fgf23 expression, even after calcitriol administration. Furthermore, box-and-whisker plots indicated that Fgf23 expression was observed in osteocytes with higher expression levels of the Fam20c, Dmp1, and Phex genes, whose inactivating mutations have been shown to cause FGF23-related hypophosphatemic diseases. These results indicate that osteocytes are heterogeneous with respect to their responsiveness to 1,25-dihydroxyvitamin D3, and sensitivity to 1,25-dihydroxyvitamin D3 is one of the characteristics of osteocytes with Fgf23 expression. It is likely that there is a subpopulation of osteocytes expressing several genes, including Fgf23, involved in phosphate metabolism.